RESTORATIVE JUSTICE: A NEW APPROACH TO RESOLVING DOMESTIC VIOLENCE - Jidatul Haz, M. Aaz; Wathoni, Lalu Muhammad Nurul; Zulkarnain, Zulkarnain; Maghfurrahman, Muhammad; Baldan Haramain, Fathur (Jurnal Al-Dustur, 2024)
Domestic Violence (a.k.a KDRT) has been identified as a form of crime that falls into the category of "hidden crime". Handling through the conventional criminal justice system often faces serious obstacles, especially because victims often experience deep trauma. In addition, when these cases are presented in court, the justice obtained is often unsatisfactory for both the perpetrator and the victim. As an alternative, the Restorative Justice approach emerged as an attempt to provide a more holistic solution. Restorative justice focuses on returning losses to victims, improving the perpetrator's behavior, and providing opportunities for perpetrators to reintegrate into society without experiencing stereotypes. In the Indonesian context, this research aims to explore more deeply the implementation of restorative justice, including its legal basis, procedures, and carry out analysis using the concept of legal pluralism proposed by Werner Menski. This research is normative juridical in nature, with data collection carried out through documentation studies and interviews. Research findings show that the implementation of restorative justice in Indonesia is supported by a strong legal foundation. However, there are still obstacles in accommodating the three elements of legal pluralism proposed by Menski. In other words, even though restorative justice has been formally recognized, its implementation still needs to be improved to more effectively achieve the desired restorative goals.